2009
DOI: 10.1111/j.1365-2702.2008.02458.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life among older stroke patients in Taiwan during the first year after discharge

Abstract: Older Taiwanese/Chinese people who suffer a stroke will likely benefit from interventions during the first 12 months after discharge and the most effective interventions may be earlier, during the first three months after discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 20 publications
6
23
1
1
Order By: Relevance
“…We argue that the quality of life of stroke survivors is influenced by these three latent variables. The results reveal that the level of stroke severity is significantly and negatively related to quality of life, which is consistent with the literature (Green & King, 2010;Howitt et al, 2011;Owolabi, 2013;Raju et al, 2010;Secrest & Zeller, 2007;Shyu, Maa, Chen, & Chen, 2009). Some female stroke survivors may encounter a functional disability that limits their daily life activities, and, in turn, influences family role and other functions, such as the ability to work, participate in community events, and perform household chores.…”
Section: Discussionsupporting
confidence: 91%
“…We argue that the quality of life of stroke survivors is influenced by these three latent variables. The results reveal that the level of stroke severity is significantly and negatively related to quality of life, which is consistent with the literature (Green & King, 2010;Howitt et al, 2011;Owolabi, 2013;Raju et al, 2010;Secrest & Zeller, 2007;Shyu, Maa, Chen, & Chen, 2009). Some female stroke survivors may encounter a functional disability that limits their daily life activities, and, in turn, influences family role and other functions, such as the ability to work, participate in community events, and perform household chores.…”
Section: Discussionsupporting
confidence: 91%
“…Shyu et al 48 emphasised the importance of intervening with stroke survivors even after their physical rehabilitation and our findings might contribute to refining interventions aimed at improving a comprehensive recovery after patients are discharged home.…”
Section: Resultsmentioning
confidence: 62%
“…32 By contrast, significantly poorer HRQoL in women was found in 5 studies. 31,33,35,37,38 The remaining 5 studies reported no association between sex and HRQoL after accounting for covariates. 18,29,34,36,39 These studies tended to adjust for PSD and functional outcomes.…”
Section: Health-related Quality Of Lifementioning
confidence: 99%